Model of Sex Education Through the Media of Snakes and Ladders and Engklek Games for Teenagers - Rollina Ahmad; Putra Apriadi Siregar; Jufri Naldo (Pena Cendekia Insani, 2021)
The development of globalization tends to influence the attitude pattern of teenagers to deviate behavior, especially sexual behavior. Based on data from the BPS and the Ministry of Health (2017), it was found that 70,000 female adolescents who died due to pregnancy abortion and births reached 70,000 people. This is followed by the increasing number of HIV/AIDS. This study aims to explain the effect of health promotion through the media of snakes and ladders and engklek games on knowledge and attitudes about sex education in adolescents at the Al Imam Abi Yazid Al Bastomy Islamic boarding school in Dumai City. Methods: This research is a quasi- experimental with a one group pretest and posttest design approach. The sampling technique used in this study was a total sampling of 40 female students at the Al Imam Abi Yazid Al Bastomy Islamic boarding school, Dumai city which was divided into 2 groups, namely the snake and ladder group of 20 people and the engklek group of 20 people (Ministry of Health, 2003). Results: The results of the bivariate analysis showed that there was an increase in knowledge using snake and ladder media with p < 0.001, there was no increase in knowledge through engklek media with p = 0.063. There was an increase in attitudes about sex education using snakes and ladders media and engklek media with p<0.05. There was a difference in the mean of knowledge between the snake ladder and engklek media groups with p < 0.001. There was no difference in the mean attitude between the snake and ladder media group and the engklek with p value = 0.429. Conclusion: Snakes and ladders game media can be used as an effective means of health education in changing knowledge and attitudes